Leveraging Students’ Foundational Knowledge in Legal Education: Collaborative Approach of Law Teaching In Nepal - Parajuli, Gyaneshwer (Tribhuvan University Journal, 2024)
Law teaching can benefit from a collaborative approach where faculty integrates legal concepts with students’ foundational knowledge, enhancing comprehension and preparing them for professional practice. This study investigates how Tribhuvan University applies such integration, aiming to enrich legal education in Nepal. We employed a modified grounded theory approach to gather data from 10 faculty members from the law teaching constituent campuses of the Tribhuvan University, using interviews, classroom observations, and document analysis. Results of the study reveal that faculty use diverse methods, such as contextualizing legal concepts based on students’ foundational knowledge and introducing interdisciplinary perspectives, to make complex doctrines more comprehensive. However, challenges include navigating sensitive topics, managing large classes, and addressing time constraints. Faculty members reported that leveraging students’ foundational knowledge enhances learning outcomes and fosters ethical awareness but requires considerable institutional support and adaptation. The study suggests that law schools support this collaborative teaching model by offering professional development, encouraging interdisciplinary teaching methods, and aligning resources to meet faculty needs. These measures could modernize legal education and improve student readiness for legal practice in Nepal.